2014
DOI: 10.1111/aab.12111
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and enzymatic evaluation of plant crude extracts derived from cinnamon and rosemary against Sclerotinia carrot rot

Abstract: The objective of this study was to assess the antifungal potential of plant crude extracts derived from cinnamon and rosemary against three isolates of Sclerotinia sclerotiorum under in vitro and in vivo conditions. The crude extracts were obtained using two different solvents including ethyl acetate (EA) and ethanol. The results showed that crude extracts of cinnamon are able to reduce mycelial growth of isolate 2 at volatile and contact phase by 35.4% and 78.2%, respectively. Furthermore, sclerotial myceliog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…In previous studies, crude extracts of some medicinal plants as well as cinnamaldehyde significantly increased the level of PPO, POD and PAL against storage carrot white mould. Moreover, sclerotia germination was markedly reduced due to the inhibitory effect of plants extract (Ojaghian, Chen, et al, ; Ojaghian, Wang, et al, , ). In conclusion, this study revealed that thyme and savoury EOs had potential to be used as resistance inducer against carrot white mould.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, crude extracts of some medicinal plants as well as cinnamaldehyde significantly increased the level of PPO, POD and PAL against storage carrot white mould. Moreover, sclerotia germination was markedly reduced due to the inhibitory effect of plants extract (Ojaghian, Chen, et al, ; Ojaghian, Wang, et al, , ). In conclusion, this study revealed that thyme and savoury EOs had potential to be used as resistance inducer against carrot white mould.…”
Section: Discussionmentioning
confidence: 99%
“…The plates were remained at 22°C. After 20 days, per cent inhibition of sclerotial viability was measured using the method and formula described by Ojaghian, Chen, et al (2014b).…”
Section: Myceliogenic Germinationmentioning
confidence: 99%
“…The S. sclerotiorum is a ubiquitous phytopathogen which infects many dicotyledonous plants including Brassica crops. Although many research have been conducted to assess control measures against Sclerotinia diseases on different crops, [4][5][6][7][8][9][10] no research has been found about nonchemical methods against tuber mustard white rot. The in vitro antifungal effect of tested chitosans and ASA was evaluated in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the percent inhibition of sclerotia formation was calculated after 15 days according to the formula S=100-(Ts×100/Cs), where: S= percent inhibition of sclerotia formation, Ts= the number of sclerotia in treatment and Cs= the number of sclerotia in control. 8 This experiment was repeated 3 times with 5 repetitions for each treatment, and the effects of different treatments were determined in a completely randomized design.…”
Section: In Vitro Effect Of Chitosans Against Sclerotinia Sclerotiorummentioning
confidence: 99%
See 1 more Smart Citation